2020
DOI: 10.1111/jnu.12584
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the Social Determinants of Health into Nursing Practice: Nurses' Perspectives

Abstract: Purpose The purpose of this study was to assess nurses’ knowledge, perceived self‐efficacy, and intended behaviors relative to integrating the social determinants of health (SDoH) into clinical practice. Design and Methods A cross‐sectional study was completed with 768 nurses working in three hospitals within a large regional healthcare system located in the Midwest. Data were collected using an adapted 71‐item SDoH Survey, which measured nurses’ confidence in and frequency of discussing the SDoH with patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 9 publications
2
37
0
2
Order By: Relevance
“…Nurses in this study identified multidisciplinary advocacy as necessary to change the health-care system 33 and this was also found in the survey study of how nurses integrate SDOH into their practice. 26 The nurses in this study did not mention that they, themselves, should join task forces or become members of organizations that advocate for health change. Berwick 34 proposes that nurses have a moral obligation to not just ensuring care for patients with illness and disease, but changing the structural issues of society that affect health, such as the SDOH.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nurses in this study identified multidisciplinary advocacy as necessary to change the health-care system 33 and this was also found in the survey study of how nurses integrate SDOH into their practice. 26 The nurses in this study did not mention that they, themselves, should join task forces or become members of organizations that advocate for health change. Berwick 34 proposes that nurses have a moral obligation to not just ensuring care for patients with illness and disease, but changing the structural issues of society that affect health, such as the SDOH.…”
Section: Discussionmentioning
confidence: 98%
“…11,25 A survey study of nurses working in acute care hospitals found that the nurses were more comfortable talking with patients about health care access than other SDOH and that the nurses' lack of knowledge of resources made them less able to meet patients' needs. 26 The nurses in this qualitative study voiced that just providing resources did not always improve care. The participants noted that patients needed to be ready for change as well as have the ability to use the resources, and nurses needed to meet the patient where they were at.…”
Section: Themes Examples Of Nurses' Interview Quotesmentioning
confidence: 92%
“…The evidence continues to suggest that nurses will require commitments to interdisciplinary training and collaboration, as well as further skill development regarding the social determinants, in order to effectively address the broader societal issues influencing health outcomes as both clinicians and advocates. 86 Box 6: Case study: the 2020 Nightingale Challenge 87 The purpose of the 2020 Nightingale Challenge is to help develop the next generation of young nurses and midwives as leaders, practitioners and advocates in health and to demonstrate both are rewarding careers.…”
Section: Rowaida Al Maaitah Drph Rn Professor and Advisor For Her Royal Highness Princess Muna El Hussein For Health And Social Developmementioning
confidence: 99%
“…For example, the American Hospital Association has laid out barriers to ensuring access to quality healthcare in vulnerable communities, including “limited federal funding, restrictive federal regulations, and a lack of collaboration and buy-in from community stakeholders” and indicates that “the most important resource may be hospital-community partnerships” [ 6 ]. Furthermore, disconnected relationships have been identified and described between clinical-community partnerships [ 7 ], and collaborative clinical-community partnerships are required to address patient social needs [ 8 ]. More work needs to be conducted to identify and describe barriers to accessing social needs-related services, especially when those needs are identified in a healthcare setting.…”
Section: Introductionmentioning
confidence: 99%